2014
DOI: 10.1016/j.jenvman.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nutrients and harmful algae in coastal waters

Abstract: Harmful algal blooms (HABs) are thought to be increasing in coastal waters worldwide. Anthropogenic nutrient enrichment has been proposed as a principal causative factor of this increase through elevated inorganic and/or organic nutrient concentrations and modified nutrient ratios. We assess: 1) the level of understanding of the link between the amount, form and ratio of anthropogenic nutrients and HABs; 2) the evidence for a link between anthropogenically generated HABs and negative impacts on human health; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(128 citation statements)
references
References 94 publications
1
99
0
7
Order By: Relevance
“…Significant deviations from the Redfield ratio indicated that this area had a highly variable concentration of nitrogen and phosphorus. A recent study clearly highlights the variations of Redfield ratios as associated with anthropogenic nutrient, yet it questions the role of this ratio in the occurrence of harmful algal blooms (HABs) (Davidson et al, 2014). Dissolved silicate concentrations were generally high and adequate for supporting the diatom proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Significant deviations from the Redfield ratio indicated that this area had a highly variable concentration of nitrogen and phosphorus. A recent study clearly highlights the variations of Redfield ratios as associated with anthropogenic nutrient, yet it questions the role of this ratio in the occurrence of harmful algal blooms (HABs) (Davidson et al, 2014). Dissolved silicate concentrations were generally high and adequate for supporting the diatom proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other algae species, the nutrient fluxes that influence HAB population dynamics are complex and vary for different species (Anderson et al 2002, 2008, Vargo 2009, Lewitus et al 2012, Iriarte et al 2013, Davidson et al 2014. Environmental factors other than nutrient loading also contribute to the formation of HABs.…”
Section: Harmful Algal Bloomsmentioning
confidence: 99%
“…Although it is increasingly clear that DON serves as an N source for both bacteria and phytoplankton (Antia et al 1991;Bronk et al 2007;Lønborg et al 2009b;Pete et al 2010), there is little information on the relative utilisation of different forms of inorganic and organic N over an annual cycle or possible links to phytoplankton community composition (Glibert et al 1982a(Glibert et al , 2016 and references therein, Davidson et al 2014Davidson et al , 2012.…”
Section: Introductionmentioning
confidence: 99%